南海北部有孔虫碳氧同位素特征与晚第四纪水合物分解的响应关系 - 曹超; 雷怀彦 (2012)
为探寻晚第四纪以来水合物分解事件在南海北部甲烷渗漏环境下有孔虫中的记录,对南海北部陆坡2个区块的沉积柱状样有孔虫碳氧同位素组成和测年分析发现,底栖有孔虫uVIgErInA SPP.碳同位素值为-2.12‰~-0.21‰,浮游有孔虫glObIgErInOIdES rubEr.氧同位素值为-3.11‰~-0.60‰,zd3、zS5 2个柱状样孔底年龄分别为26 616、64 090 A,对应了氧同位素Ⅲ、Ⅳ期末期,有孔虫碳同位素负偏的层位与氧同位素Ⅱ、Ⅳ期(冷期)层位相对应,负偏程度达到了-2‰,与布莱克海台和墨西哥湾等地区晚第四纪沉积层中有孔虫碳氧同位素组成相似。分析认为:研究区是典型的甲烷渗漏环境,该区在氧同位素Ⅱ、Ⅳ期,由于全球海平面下降,导致海底压力减小,天然气水合物分解释放,具轻碳同位素的大量甲烷释放进入海底溶解无机碳(dIC)池并记录在有孔虫壳体内,造成有孔虫碳同位素负偏;同时在有孔虫负偏层位黄铁矿和自生碳酸盐较发育,进一步证实了有孔虫碳同位素受甲烷影响较大,而海洋生产力的降低和早期成岩作用对有孔虫碳同位素负偏的影响较小。 To search the records of the gas hydrate decomposition events under methane seepage condition since the late Quaternary,carbon and oxygen isotopes analysis and radiometric dating of foraminifera from sediment cores collected from three different blocks of the northern slope of the South China Sea are carried out.The results show:1) the carbon isotope value of benthic foraminifera Uvigerina spp.is-2.12 ‰ to-0.21 ‰ and oxygen isotope value of planktonic foraminifera Globigerinoides ruber is-3.11 ‰ to-0.60 ‰;2) the age of the two cores at the bottom of ZD3 and ZS5 drills are 26 616 a and 64 090 a respectively,corresponding to the early oxygen isotope stage Ⅲ and the end of Ⅳ;3) negative-skewed layer of carbon isotope(up to-2 ‰) corresponds to that of oxygen isotope stage Ⅱ(cold period);4) the foraminifera oxygen isotopic compositions are similar to those from the Late Quaternary sediments of Blake Ridge and the Gulf of Mexico.According to our analysis,the reasons include :1) the study area is under a typical methane seep environment in the area at oxygen isotope stageⅡ;2) due to global sea-level fall,water pressure at the sea floor decreases,gas hydrate decomposed and released;3) large amount of light carbon isotopes of methane were released into the sea inorganic carbon(DIC) pool and were recorded in the foraminifera shell.Pyrite layers developed in the negative bias layers of foraminifera further supports our views that the carbon isotope of the foraminifera were affected by methane more intensely than by the reduction of marine productivity and by early diagenesis. 国家“973”计划项目(2009CB219501);国家自然科学基金项目(40976035)